Perancangan Sistem Pendukung Keputusan Penerimaan Beasiswa Menggunakan Metode Analytical Hierarchy Process (AHP), Simple Additive Weighting (SAW) dan Elimination Et Choix Traduisant la Realite (ELECTRE) - Ali, Muhammad Rifqi; Andryana, Septi; Hidayatullah, Deny (KITA Institut, 2021)
In the world of education, scholarships are financing or subsidies provided by the government, companies, universities, and other educational institutions. This study aims to design and build a decision support system to assist and facilitate the school in determining prospective recipients of scholarship assistance for poor and high achievers with the criteria determined by the scholarship organizer. With this, the researcher designed and built a decision support system using the Analytical Hierarchy Process (AHP) method which was then compared by the Imple Additive Weighting (SAW) and Elimination Et Choix Traduisant la Realite (ELECTRE) method. So that the results of the design of this system are able to assist in determining prospective scholarship recipients. The comparison of the 3 methods shows the results of the ranking of criteria that are slightly different, but basically, the 3 methods can be used properly to solve the problem of determining the scholarship recipient.Keywords:Support System, Analytical Hierarchy Proses (AHP), Simple Additive Weighting (SAW) dan Elimation Et Choix Traduisant la Realite (ELECTRE).